Variability in Structure of University Pulmonary/Critical Care Fellowships and Retention of Fellows in Academic Medicine - Nadig, Nandita R. (Ann Am Thorac Soc, 2015)
Introduction: Individual fellowship programs are challenged to find a format of training that not only meets the Accreditation Council for Graduate Medical Education requirements, but also grooms fellows to be trusted clinicians, and encourages them to enter academic careers. This study was undertaken as part of an internal effort to evaluate and revise the program structure of the pulmonary/critical care medicine fellowship at the Medical University of South Carolina. Our objectives were to characterize variation in the training structure and specifically research opportunities of university pulmonary/critical care medicine fellowship programs, and to identify factors associated with fellow retention in academic medicine and research. Methods: A 30-item survey was developed through rigorous internal review and was administered via email. Descriptive statistics, Cronbach’s alpha, correlations, Wilcoxon sign-rank test, and ANOVA were carried out. Results: We had a response rate of 52%. Program directors reported that, within the past 5 years, 38% of their fellows remained in academic medicine and 20% remained in academics with significant research focus. We found a statistically significant association between obtaining a master’s degree and remaining in academics (r = 0.559; P < 0.008). The survey also revealed statistically significant relationships between scholarly requirements (grant proposals, peer-reviewed original research projects) and the percent of fellows who graduated and remained in academics. Conclusions: This survey offers some insights that may be useful to fellowship program directors. In particular, advanced education in research and maximizing scholarly activities might be associated with increased academic retention among fellowship trainees.